Optimalisasi Penyelenggaraan Statistik Sektoral sebagai Upaya Pemenuhan Data Statistik Berkualitas di Indonesia - Dewy Sarihastuti (Jurnal Syntax Admiration, 2024)
The development of data needs in Indonesia has increased awareness of the importance of quality data in supporting development planning and implementation. The government responded by issuing Presidential Regulation Number 39 of 2019 concerning One Data Indonesia (SDI), which aims to produce accurate, up-to-date, and accountable data. However, the implementation of sectoral statistics still faces challenges, including the low national Statistical Development Index (IPS) in 2023 which is in the less than ideal category with a value of 1.78 on a scale of 5.00. This study aims to identify the root causes of the suboptimal implementation of sectoral statistics by Ministries/Institutions/Regions/Agencies (K/L/D/I) and to prepare policy recommendations for improvement in order to realize quality sectoral statistics. The methodology used includes literature studies, secondary data analysis from the results of the Evaluation of Sectoral Statistics Implementation (EPSS), interviews with related teams, and review of laws and regulations. The results of the analysis show several main causal factors: the failure to implement comprehensive sectoral statistics guidance by the Central Statistics Agency (BPS); not all K/L/D/I submit independent assessments so that the progress of sectoral statistics implementation cannot be measured; and budget limitations to support sectoral statistics activities in the regions. To overcome these problems, it is recommended that BPS formulate clear regulations on sectoral statistics development guidelines and increase active development to K/L/D/I. In addition, the Ministry of Home Affairs is expected to encourage regional governments to provide adequate budgets through official circulars. In conclusion, improving the quality of sectoral statistical data requires collaborative efforts between BPS, K/L/D/I, and regional governments. Intensive development, comprehensive evaluation, and adequate budget support are the keys to realizing quality statistical data in accordance with the One Data Indonesia principle.